Evaluating the tozzi classification system in diaphragm surgeries for advanced ovarian cancer: Clinical applicability and perioperative outcomes - Divya Panyam Vuppu; Priya Bhati; Saumya Gupta; Sheejamol V S; Nitu Puthenveettil (Cancer Treatment and Research Communications)
Background: Over 70 % of advanced ovarian cancer cases involve metastasis to the peritoneum, diaphragm, and liver. Standardised diaphragm surgeries are vital for achieving complete cytoreduction and enhancing patient prognosis. Aim: This study evaluates the clinical utility of Tozzi’s classification for diaphragm surgeries and examines perioperative outcomes in advanced ovarian cancer debulking. Methods: Patients who underwent diaphragm surgery during cytoreductive procedures for ovarian cancer were classified using Tozzi’s classification based on disease extent, and liver mobilisation and perioperative outcomes were analysed. Results: Among 38 patients (71 % stage III; 52.6 % interval surgeries), 39.4 % were Type I, 28.9 % Type II, and 31.5 % Type III. Ascites was more common in Type II (77.8 %, p = 0.04), while Type III had more imaging-detected lesions (83.3 %, p = 0.03). Type III surgeries required longer durations (405 ± 136 min, p = 0.04) and more intraoperative interventions (58.3 %, p = 0.01). ICU care was needed in 50 % of cases, with a median stay of two days, mainly for Type III. Pulmonary complications occurred in 10.5 %, and the median hospital stay was six days. Conclusion: Tozzi’s classification predicts surgical complexity and morbidity, particularly for Type III cases, aiding surgical planning and optimising patient outcomes.